The interrelationships of three change of direction ability tests in elite female volleyball players: an exploratory study - Wright, W. C.; Aguiar, E. J.; Winchester, L. J.; Fedewa, M. V.; Fields, A. D.; Esco, M. R. (Sports, 2025)
Background: The purpose of this exploratory study is to evaluate the relationships between commonly used change of direction COD tests (t-test, L-drill, and 5-10-5 shuttle) in Division I female volleyball players. Methods: Sixteen Division I female volleyball players (age = 19.4 ± 1.4 years, height = 176.2 ± 10.6 cm, weight = 71.5 ± 11.1 kg) participated in this study and completed three trials of the t-test, L-drill, and 5-10-5 shuttle in a randomized order. The best time for each test was recorded and analyzed. Pearson product correlations were used to determine the interrelationships between each of the three COD tests. Additionally, a composite score was created by summing the best performances of the three drills. The relationship between each test and the composite score was also established via Spearman rank correlations. Results: The mean ± standard deviation for time to complete each test was 10.9 ± 0.7 s for the t-test, 8.6 ± 0.3 s for the L-drill, and 4.9 ± 0.2 s for the 5-10-5. Statistically significant correlations were shown between the t-test and L-Drill (r = 0.89, p < 0.001,), between the L-drill and 5-10-5 Shuttle (r = 0.91, p < 0.001), and between the 5-10-5 Shuttle and t-test (r = 0.83, p < 0.001). In addition, each COD test significantly correlated with the composite score (p = 0.92-0.95). Conclusion: The high degree of agreement between the three COD tests suggests that any one of them could be utilized for testing COD ability in female volleyball players.